Peer Group Learning Method to Improve the College Student’s Achievement - Solfema, Solfema; Wahid, Syafrudin (Universitas Negeri Semarang, 2018)
This research aimed to find out the effectiveness of peer group learning method in improving the college students’ achievement. This research uses one group pretest and posttest design. The population is non-formal education students of State University of Padang who take Education Statistics Subject in January-June 2017, consists of two classes each of which is control group and experimental group. There are 30 students in the control group and 41 students in the experimental group. The data obtained from the students’ learning result during January-June 2017 and analyzed using t-test statistical technique. The purposes of the research are (1) peer tutor is a strategy to help fulfilling the students’ need; (2) peer tutors will be proud of their role and they will learn from their experiences as tutor; and (3) peer tutor’s help can eliminate the students’ clumsiness. The research findings indicate that the students’ learning result with conventional learning method is unsatisfactory, the peer group learning method can improve the students’ learning result, and there is a significant difference between the students’ achievement learned with the conventional method and learned with the peer group method.